Advances in Angle-Only Filtering and Tracking in Two and Three Dimensions - Mallick, Mahendra; Tharmarasa, Ratnasingham (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Two-dimensional bearing-only filtering (BOF) arises in many real-world tracking problems, including underwater tracking using a passive sonar, aircraft surveillance using a passive radar, navigation of a robot using a passive sonar, and undersea exploration of natural resources using sonar. BOF using a single sensor is also a challenging nonlinear filtering problem due to poor observability and the nonlinear measurement model. This filtering problem and associated tracking problem have been studied extensively. Three-dimensional angle-only filtering (AOF) is a two-dimensional counterpart of BOF . Real-world AOF problems include passive ranging using an infrared search and track (IRST) sensor, passive sonar, passive radar in the presence of jamming, ballistic missile and satellite tacking using a telescope, satellite to satellite passive tracking, and missile guidance using bearing-only seekers. The number of publications in the AOF and angle-only tracking in 3D is rather limited compared with the corresponding problems in 2D.